Art Conservation and its Curriculum as Relational Mystery - Kalin, Nadine M.; Peck, Scott (Journal of the Canadian Association for Curriculum Studies, 2025)
Art conservation practices tend to adhere to Eurocentric reductionism and rationalism that have dominated Western sciences and education, negating subjectivity and experience as knowledge sources. Aoki called for mysterious and generative middles between planned and live(d) curriculum to be indwelled through meditation, expanding curriculum to include individual lifeworlds and relations. This study mobilizes Foucauldian death meditation to destabilize and further expand curriculum by indwelling on death in life from the mysterious middles between human art conservators and more-than-human art objects. Bringing together neo-materialist and Indigenous perspectives, we reconfigure current limits of art conservation to consider agency, intra-action and permeability of human and non-human lifedeath. In the care of artwork by conceptual artists Komar and Melamid—intentionally created to disintegrate—meditations of attending and mourning reach toward more response-able forms of art conservation practice and curriculum. We propose an art conservation curriculum of relational mystery using death meditation entangled with conundrums of art mourning to deepen students’ enchantment with unfathomable aspects of lifedeath, thereby invigorating teaching and conserving with mystery.